2018
DOI: 10.4236/ojog.2018.812119
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemio-Clinic Profile of Clandestine Abortion at Saint Joseph Hospital (Kinshasa)

Abstract: Objective: To identify the epidemiologic profile of the woman having practiced the clandestine abortion, to determine the frequency and the complications of the clandestine abortion and to evaluate the prognosis of the clandestine abortion in our area. Method: The present study is descriptive and retrospective covering the period from January 2017 to December 2017, the one year period. On 118 patients received in the service for clandestine abortion, 60 were retained for the study. The 58 other files were excl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…Males are more affected, regardless of race, region or socio-economic level [9]. This result is in line with those of KABONGO and KALENGAYI in the DRC [8], MUBIKAYI and KALENGAYI in the DRC [7], ADAM et al in Ethiopia [9], SCHAMOON et al in Iraq [2] and ANTONIO in Brazil [12], who all found a high frequency of HL in males. In Great Britain, a multicentre epidemiological study carried out in several regions (England, Scotland, Wales) showed a variable incidence rate between the two sexes, with 2.65/100,000 inhabitants for men and 1.81/100,000 inhabitants for women [13].…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Males are more affected, regardless of race, region or socio-economic level [9]. This result is in line with those of KABONGO and KALENGAYI in the DRC [8], MUBIKAYI and KALENGAYI in the DRC [7], ADAM et al in Ethiopia [9], SCHAMOON et al in Iraq [2] and ANTONIO in Brazil [12], who all found a high frequency of HL in males. In Great Britain, a multicentre epidemiological study carried out in several regions (England, Scotland, Wales) showed a variable incidence rate between the two sexes, with 2.65/100,000 inhabitants for men and 1.81/100,000 inhabitants for women [13].…”
Section: Discussionsupporting
confidence: 76%
“…HLc of the mixed cellularity type is predominant in all age groups, except in the 3 to 10 years of age group where the scleronodular type is more prevalent. Studies by KABONGO and KALENGAYI [8] and MUBIKAYI and KALENGAYI [7] in the DRC also revealed a predominance of the mixed cellularity type in all age groups. On the other hand, NAGPAL in the USA observed a predominance of the sclerodular type in all age groups, except in the 0-14 age group where he found a predominance of the mixed cellularity subtype [17].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations